ANALISIS PENERAPAN GOOD GOVERNANCE PADA DIREKTORAT JENDERAL PAJAK (STUDI KASUS: KPP PRATAMA MALANG SELATAN) - Hasibuan, Dynda Damaiani (Jurnal Ilmiah Mahasiswa FEB, 2017)
This qualitative study aims to identify the application of good governance in Small Tax Office of Malang Selatan, as the unit vertically below the Directorate General of Tax, based on the principles and indicators of good governance issued by Bappenas through case study approach. The principles are visionary, openness and transparency, participation, accountability, rule of law, democracy, professionalism and competency, responsiveness, efficiency and effectiveness, decentralization, private sector and civil society partnership, and commitment to environmental protection. The data are obtained through interviews, observation, literary research, and documentation. This study finds that Small Tax Office of Malang Selatan has applied good governance principles well.Keywords: good governance, directorate general of tax